PERANCANGAN IKLAN LAYANAN MASYARAKAT PENYALAHGUNAAN NARKOBA MELALUI MEDIA MOTION GRAPHIC DI KOTA PADANG - TESYA SITI MEDINA, Eliya Pebriyeni, S.Pd., M.Sn., San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Public service announcement, usually called PSA, is used to convey information, to urge or to educate the public, and the final goal of it is not to get the economic advantage, but rather the social advantage. One of the examples of public service announcement is the announcement about drug abuse delivered through motion graphic, which will be available in Padang in the future.At this present, drug abuse is something common for people in Indonesia especially in Padang. One of the causes of being easily entangled in the drug abuse is the lack of knowledge and information about it. The information should be given in such a way that it is easily understood. One of the ways is by using public service announcement with motion graphic.Designing public service announcement about drug abuse with motion graphic aimed at informing societies especially those from the age of 19 to 45 about the dangers of consuming drugs which lead them to addiction. Besides, it provided new solution in delivering the announcement about drug abuse using motion graphic.Other than using motion graphic as the main medium, this design also used other supporting media such as poster, x-banner, t-shirt, pin, mug, tote bag, and sticker as the supplements to the main medium and the promotional media.Keywords: Public Service Announcement, Motion Graphic, Drug.